The Use of the Story Telling Method to Improve Student Speaking Ability - Baihaqi, Yasmika; Prasasti, Ian Harum; AS, Ladyana Alvin (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
This study aims to find evidence of the method learning storytelling can improve students speaking ability at SMA Negeri 5 Metro. The total sample involved was 59 students. The method used in this studys a quasi-experimental. The result of Data analysis showed that the post-test mean score was higher than the pre-test (54.06 > 44.27). This shows the results of the analysis which show that the t value obtained is higher than the t table (17,067 > 2,048). then the second data shows that the t-test value obtained is greater than the t-table (3,269 > 2.021), it can be concluded that learning to speak using storytelling in the even semester of class XI SMA Negeri 5 Metro can improve abilities. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that the use of story telling provides an improvement in students' speaking.